PROFIL PASIEN HIV DI POLIKLINIK VCT RSUD ULIN BANJARMASIN TAHUN 2021-2022 - Darwis, Muhammad Wisnu Adi; Zaitun, Nani; Rahmiati, Rahmiati; Nur’amin, Hendra Wana; Hayatie, Lisda (Homeostasis, 2024)
Abstract: Human Immunodeficiency Virus is a major threat and problem in the health sector. The aim of the study was to describe the profile of HIV patients at the VCT Polyclinic of Ulin Banjarmasin Hospital in 2021-2022. The research method is descriptive observational using secondary data from the VCT Polyclinic registration books and PDE. The results showed that there were 147 HIV cases with the highest cases in 2022 totaling 75 patients (51%). Based on variables, the most cases in 2021 were age groups 17-25 and 26-35 years (26%), male gender (72%), Banjarmasin domicile (56%), working status (44%), secondary education level (47%), key population MSM (22%), heterosexual transmission (26%), clinical stages 3 and 4 (24%), opportunistic tuberculosis infection (15%), first line therapy regimen (93%), and CD4 count <100 cells/mm3 (32%). Whereas in 2022, the highest number of cases were in the age group of 26-35 years (40%), male gender (67%), Banjarmasin domicile (59%), working and non-working status (36%), no school education (27%), key population of MSM (34%), homosexual transmission (40%), clinical stage 4 (45%), opportunistic tuberculosis infection (15%), first line therapy regimen (97%), and CD4 count <100 cells/mm3 (27%). The number of cases of opportunistic infections based on the highest CD4 count was tuberculosis with 7 patients in 2021 and 12 patients in 2022 with the highest CD4 count for the appearance of opportunistic infections, namely <100 cells/mm3 (74%).  Keywords: HIV, patients profile, opportunistic infection, key populations, Banjarmasin. Abstrak: Human Immunodeficiency Virus merupakan ancaman dan permasalahan utama bidang kesehatan. Tujuan penelitian adalah mendeskripsikan profil pasien HIV di Poliklinik VCT RSUD Ulin Banjarmasin tahun 2021-2022. Metode penelitian yaitu observasional deskriptif menggunakan data sekunder dari buku registrasi Poliklinik VCT dan PDE. Hasil penelitian menunjukkan kasus HIV sejumlah 147 pasien dengan kasus tertinggi tahun 2022 sejumlah 75 pasien (51%). Berdasarkan variabel, kasus terbanyak tahun 2021 yaitu kelompok umur 17-25 dan 26-35 tahun (26%), jenis kelamin laki-laki (72%), domisili Banjarmasin (56%), status bekerja (44%), tingkat pendidikan menengah (47%), populasi kunci LSL (22%), penularan heteroseksual (26%), stadium klinis 3 dan 4 (24%), infeksi oportunistik tuberkulosis (15%), regimen lini terapi pertama (93%), dan jumlah CD4 <100 sel/mm3 (32%). Sedangkan tahun 2022 kasus terbanyak yaitu kelompok umur 26-35 tahun (40%), jenis kelamin laki-laki (67%), domisili Banjarmasin (59%), status bekerja dan tidak bekerja (36%), pendidikan tidak sekolah (27%), populasi kunci LSL (34%), penularan homoseksual (40%), stadium klinis 4 (45%), infeksi oportunistik tuberkulosis (15%), regimen lini terapi pertama (97%), dan jumlah CD4 <100 sel/mm3 (27%). Jumlah kasus infeksi oportunistik berdasarkan jumlah CD4 terbanyak yaitu tuberkulosis sebanyak 7 pasien di tahun 2021 dan 12 pasien di tahun 2022 dengan jumlah CD4 terbanyak munculnya infeksi oportunistik yaitu <100 sel/mm3 (74%). Kata-kata kunci: HIV, profil pasien, infeksi oportunistik, populasi kunci, Banjarmasin.